Oxygen-ozone therapy is at a cross-road (Ozone Therapy Global Journal, 2011)
Oxygen-ozone therapy is slowly coming into age and it is being used in many Countries.However, while the treatm ent of hernial disk b y s imply injecting a little vol um e ofgaseous O2-O3 ins ide t h e n u cleus pulpos u s is a great s u cc e ss , the us e o f theso- called major oz o n a ted-autohemot h e rap y ( M-O3-AHT ) , consi sting of 200 mLof autologous b l o o d treated with g a seous O2- O3 mixture and rapidly infused intothe donor, lags behind due to a number of reasons among which lack of standardization,need of numerous treatment, lack of knowledge, skepticism and even denial. Skepticism,which is fundamental to the scientific method, can be overcome only by showing thevalidity of M-O3AHT in controlled and randomized clinical trials on specific diseases,as correctly requested by the official Medicine. This paper aims to emphasize all theproblems plaguing this therapeutic modality and to suggest remedies to enhance itsprogress and development.